2021
DOI: 10.3389/fcell.2021.670825
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Activity and Cell Proliferation Are Coupled to Extracellular Vesicle Release in Multiple Organoid Models

Abstract: Extracellular vesicles (EV) are considered as a potential tool for early disease diagnosis; however, factors modifying EV release remain partially unknown. By using patient-derived organoids that capture the cellular heterogeneity of epithelial tissues, here we studied the connection between the Wnt-producing microniche and EV secretion in multiple tissues. Although nearly all cells in pancreatic ductal (PD) and pancreatic ductal adenocarcinoma (PDAC) samples expressed porcupine (PORCN), an enzyme critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Using canine-specific LGR5 probes, we previously detected ISCs within the intestine organoid crypts [ 30 ], demonstrating that proliferation is restricted to crypt-like budding structures [ 64 ]. Ki67 has been used as a proliferation marker as its expression is strongly associated with proliferation and growth [ 65 , 66 ]. Other intestinal stem cell markers and genes associated with proliferation, notably proliferating cell nuclear antigen ( PCNA ), prominin 1 ( PROM1 ), HOP homeobox ( HOPX ), and olfactomedin 4 ( OLFM4 ), were also increased in LPS-treated IBD intestinal organoids and tumor enteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Using canine-specific LGR5 probes, we previously detected ISCs within the intestine organoid crypts [ 30 ], demonstrating that proliferation is restricted to crypt-like budding structures [ 64 ]. Ki67 has been used as a proliferation marker as its expression is strongly associated with proliferation and growth [ 65 , 66 ]. Other intestinal stem cell markers and genes associated with proliferation, notably proliferating cell nuclear antigen ( PCNA ), prominin 1 ( PROM1 ), HOP homeobox ( HOPX ), and olfactomedin 4 ( OLFM4 ), were also increased in LPS-treated IBD intestinal organoids and tumor enteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the effect of genetics in the production of EVs is suggested by studying the role of Apc mutation in activation of the Wnt pathway and EV production as the downstream result [ 122 ]. Similarly, in a study by Sándor et al on lung adenocarcinoma organoids, the role of the Wnt pathway on cell proliferation and EV secretion has been indicated [ 124 ]. In a recent study by Taha et al, it has been indicated that matrix metalloproteinase 3 (MMP3) has a crucial role in maintaining the physical integrities of EVs and any reduction in MMP3 results in disorganization of EV structures, inhibition of their protumorigenic properties, and finally a reduction in tumor proliferation and progression [ 116 ].…”
Section: Organoids As 3d Culture Models For Evs Analysismentioning
confidence: 97%
“…Sàndor and coworkers used LUAD organoids to identify a Wnt-producing microniche composed by both cancer cells and fibroblasts, which was able to influence cancer cell proliferation and extracellular vesicle release. The same authors identified a CD133high subpopulation in LCOs with stem cell characteristics, such as elevated self-renewal and Wnt activity or responsiveness [ 56 ]. Finally, Ma and coworkers analyzed the gene expression profiles of LCOs derived from LUAD and LUSC, finding a differential regulation of pathways involved in immune regulation, inflammation, MAPK, and Rap1 activation between the two histotypes [ 57 ].…”
Section: Preclinical Applications Of Lung Cancer Organoidsmentioning
confidence: 99%